Complexity Theory and Ecofeminism: Looking At a Coalition - Woodill, Sharon (Atlantis, 2010)
Complexity theory may provide a helpful conceptual toolbox for understanding interpenetrated social and material systems of oppression as posited by ecofeminism; however, successful coalition demands careful consideration of the epistemic implication of complexity theory. Curdled logic can facilitate the epistemic move from monism to plurality that such a coalition would require.